2000
DOI: 10.1086/317128
|View full text |Cite
|
Sign up to set email alerts
|

A High‐Sensitivity Measurement of the MeV Gamma‐Ray Spectrum of Cygnus X‐1

Abstract: The Compton Gamma-Ray Observatory (CGRO) has observed the Cygnus region on several occasions since its launch in 1991. The data collected by the COMPTEL experiment on CGRO represent the most sensitive observations to date of Cygnus X-1 in the 0.75-30 MeV range. A spectrum accumulated by COMPTEL over 10 weeks of observation time shows significant evidence for emission extending out to several -2 -MeV. We have combined these data with contemporaneous data from both BATSE and OSSE to produce a broad-band γ-ray sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
120
3
9

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(146 citation statements)
references
References 57 publications
14
120
3
9
Order By: Relevance
“…Observations with the INTEGRAL satellite have confirmed the existence of a supra-thermal tail in the spectrum (Cadolle Bel et al 2006). So-called hybrid thermal/non-thermal models from Poutanen & Svensson (1996) and Coppi (1999) have been used to fit the observed spectrum (McConnell et al 2000;Cadolle Bel et al 2006). These models consider a hybrid pair plasma with a non-thermal component.…”
Section: Application To Cygnus X-1mentioning
confidence: 99%
See 1 more Smart Citation
“…Observations with the INTEGRAL satellite have confirmed the existence of a supra-thermal tail in the spectrum (Cadolle Bel et al 2006). So-called hybrid thermal/non-thermal models from Poutanen & Svensson (1996) and Coppi (1999) have been used to fit the observed spectrum (McConnell et al 2000;Cadolle Bel et al 2006). These models consider a hybrid pair plasma with a non-thermal component.…”
Section: Application To Cygnus X-1mentioning
confidence: 99%
“…These models consider a hybrid pair plasma with a non-thermal component. In particular, using the EQPAIR code, McConnell et al (2000) concluded that either the magnetic field in Cyg X-1 is substantially below equipartition (at least to within an order of magnitude) or the observed photon tail has a different origin than that related to locally accelerated electrons.…”
Section: Application To Cygnus X-1mentioning
confidence: 99%
“…Cyg X-1 was observed by the instruments aboard the Compton Gamma Ray Observatory on several occasions during the first three cycles (1991)(1992)(1993)(1994), when the source was in a low/hard state (McConnell et al 2000). COMPTEL measured an energy spectrum described by a simple power-law with photon index 3.3 ± 0.4, between 0.75 and 5 MeV.…”
Section: The Search For Gamma Ray Emissionmentioning
confidence: 99%
“…During the first three cycles of observation (1991)(1992)(1993)(1994) of the Compton Gamma Ray Observatory (CGRO), the source, in hard state, was detected by COMPTEL only between 2 and 5 MeV (see McConnell et al 2000, for details). EGRET did not detect the source during that observation and the upper limit to the flux is of the order of 10 × 10 −8 ph cm −2 s −1 , posing no need for a high-energy cut-off.…”
Section: Introductionmentioning
confidence: 99%
“…We also took into account the effect of secondary pairs created by photon-photon pair production. Figure (1) shows the total SED together with the spectrum of Cygnus X-1, detected by COMPTEL McConnell et al (2000) and the radio detection of the jet by Stirling et al (2001).…”
Section: Static Corona Modelmentioning
confidence: 99%